2018
DOI: 10.1002/asia.201801180
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic synthesis of lactones and lactams

Abstract: Cyclic esters and amides (lactones and lactams) are important active ingredients and polymer building blocks. In recent years, numerous biocatalytic methods for their preparation have been developed including enzymatic and chemoenzymatic Baeyer–Villiger oxidations, oxidative lactonisation of diols, and reductive lactonisation and lactamisation of ketoesters. The current state of the art of these methods is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Enzymatic synthesis of lactones as polyester building blocks gained great interest as an environmentally sustainable alternative to current chemical methods. The most common biocatalysts to produce lactones are Baeyer–Villiger monooxygenases (BVMOs) and alcohol dehydrogenases (ADHs) . These two classes of enzymes require cofactor NAD(P)H regeneration, making these strategies less suitable for commercial applications.…”
Section: Results Of Aox*‐catalyzed Conversions Of Diols and Other Alcmentioning
confidence: 99%
“…Enzymatic synthesis of lactones as polyester building blocks gained great interest as an environmentally sustainable alternative to current chemical methods. The most common biocatalysts to produce lactones are Baeyer–Villiger monooxygenases (BVMOs) and alcohol dehydrogenases (ADHs) . These two classes of enzymes require cofactor NAD(P)H regeneration, making these strategies less suitable for commercial applications.…”
Section: Results Of Aox*‐catalyzed Conversions Of Diols and Other Alcmentioning
confidence: 99%
“…[135b] w-Hydroxy acids and lactones were also produced by oxidation of diols with ADH or alcohol oxidase. [136] Besides oxidation from alcohols,a cids can also be produced by biocatalytic oxidation of easily available hydrocarbons.T he Park group developed the cascade oxidation of the C=Cbond in oleic acid and linoleic acid into the diacids or w-hydroxy acids,y et at ar elatively low concentration. [44,137] TheL ig roup reported the whole-cell cascade oxidation of styrene to (S)-mandelic acid, (S)-or (R)-phenylglycine,a nd phenylacetic acid in up to 140 mm ( % 20 gL À1 ).…”
Section: Acid Production Via Hydrolysis Of Esters/amidesmentioning
confidence: 99%
“…However, these substrates are most likely not the natural substrates of CYP116B46, since uncoupling with decanoic acid was 11.5 % and the total turnover numbers (TTNs) were 242 with decanoic acid and 27 with dodecanoic acid. Terminal hydroxylation is the main focus of reports on n ‐alkane and fatty alcohol hydroxylation, with very few reports on the latter, despite the potential that not only diterminal diols but also internal alkane diols hold for the synthesis of polymers and even lactones and lactams . Recently, Sakai et al.…”
Section: Methodsmentioning
confidence: 99%
“…Terminal hydroxylation is the main focus of reports on n-alkane and fatty alcohol hydroxylation, with very few reports on the latter, [5,6] despite the potential that not only diterminal diols but also internal alkane diols hold for the synthesis of polymers [5] and even lactones and lactams. [7] Recently, Sakai et al reported that CYP505D6, a self-sufficient P450 from the white-rot fungus Phanerochaete chrysosporium, preferably hydroxylates 1-dodecanol and dodecanoic acid at the sub-terminal positions (w-1 to w-3), but also yielded the in-chain hydroxylated products (w-4 to w-7) as minor products. [8] However, to date, no catalysts have been described for the regioselective in-chain oxyfunctionalization of n-alkanes, where no directing functional group is available.…”
mentioning
confidence: 99%